Medical terminology in new age Serbia: over 150 years of existence - Ankica, (General Practice, 2023)
The marking of the anniversary in 2022 wasof great importance for medical terminology in Serbia. Afterthe first, short-lived institutionalization in the Društvo srpskeslovesnosti in 1842 this topic became part of the work assignmentsand activities of an institution, for the second time.This time it was for the Serbian Medical Society (SMS) rightafter its foundation in 1872. Every randomness in this areawas disabled by very clear and precise attitudes establishedby the first Constitution of SMS. In this area of our medicalscience, besides founders and first members of SMS, thespecial place belongs to physicians Jovan Stejic, Milan Jovanovic-Batut, Radivoje Pavlovic, Aleksandar Kostic, AleksandarBelic, and others.Nowadays, medical terminology is no longer a part ofthe Constitution of the SMS. It is not yet clear how this happened,nor who, if any, other institution, has taken this hugeobligation and responsibility for the development, improvement,and maintenance of medical terminology in the Serbianlanguage. Its creation needs the cooperation of professionalsfrom different walks of education, first of all, physiciansand experts in the Serbian language, because it is a matter offoundation, almost identity values. It is necessary to makeproper terms and interpret them precisely. The absence of thisinevitably leads, not only to a standstill, but collapsing of thealready achieved that would instead of enriching only impoverishthe Serbian language.
Keywords: medical terminology; Serbian language